Global Oral Health- Seeing My Reflection in a Changing Tide - Brittany Seymour (Journal of the California Dental Association)
Global oral health is an evolving field with perhaps the most significant global policy milestones happening in recent years. Through a first-person account of one global health professional’s evolving career, this discussion article considers landmark events and reports from the past 15 years that have shaped modern day global health and global oral health. The historical review highlights impactful successes and ambitious policy goals while also posing challenging questions confronting dentistry today. It concludes with a call to action, urging the dental profession to capitalize on policy opportunities that can change the future of the profession and global oral health.